Prevalence and impact of misdiagnosed drug allergy labels among patients with hereditary angioedema - Wong, Jane Chi Yan; Cheong, Noel; Lau, Chak Sing; Li, Philip Hei (Frontiers in Allergy, 2022)
Introduction Hereditary angioedema (HAE) is a rare condition with presents with episodic attacks of angioedema, which is often misdiagnosed as allergy, and associated with significant morbidity and mortality. Misdiagnosed drug allergy (DA) labels are also associated with a multitude of adverse clinical outcomes. However, the prevalence and impact of incorrect DA labels on HAE remains unknown. Methods Data from the clinical records of all HAE patients in Hong Kong were collected and analysed. All HAE patients with DA labels on their medical records were recruited to proceed with DA testing, including confirmatory drug provocation tests (DPT). Results Nine (22%) out of a total of 41 HAE patients carried at least one DA label. Five of nine (56%) patients had more than 1 DA label and there was a total number of 16 DA labels. The most common DA label was to beta-lactams (37.5%). Presence of DA label was associated with delay in HAE diagnosis (23.8 ± 11.1 vs. 10.2 ± 14.3 years, p = 0.012), likelihood of HAE attacks (100% vs. 46.9%, p = 0.005) and rate of hospitalization (3.78 ± 2.68 vs. 1.32 ± 2.61, p = 0.022) per year. All (100%) of all DA labels were disproven and removed after confirmatory DPT were performed. Conclusion DA labels are prevalent among HAE patients but are frequently misdiagnosed and mislabelled. Misdiagnosed DA are associated with delay in HAE diagnosis as well as adverse clinical outcomes. Immunologists/allergists should consider pre-emptively reviewing and investigate every suspicious DA label, especially among HAE patients.